SECURING PERSONAL DATA IN E-KYC: VITAL FOR DIGITAL ECONOMY GROWTH - Fitriyanti, Fadia; Devty, Stephanie; Putri, Syahmilian; Thora, Reyhan Edgarda (Fakultas Hukum, Universitas Diponegoro, 2024)
As the world enters the era of Industrial Revolution 4.0, Indonesia's creative industry has tremendous potential for economic growth. During this transformation, the digital economy of financial services, such as e-KYC (electronic Know Your Customer), has emerged as a crucial element for authenticating banking and financial technology customers. To safeguard consumer data, e-KYC procedures typically employ electronic methods, such as facial recognition and biometric scanning. In addition to qualitative analysis and secondary data, this research employs legal methodology to evaluate the protection of consumers’ personal dataThis study also aims to better understand the impact of the Personal Data Protection Law on the e-KYC process and its function in driving the growth of the digital economy. This study contributes to a deeper understanding of Indonesia’s evolving digital landscape and economic outlook by emphasizing the legal framework governing consumer data protection. The results of this study indicate that customer personal data in the implementation of e-KYC are already protected by the newly enacted Personal Data Protection Law No. 27 of 2022.